Revision of Proteaceae macrofossil record from Patagonia, Argentina - González, Cynthia Cristina; Gandolfo, Maria A.; Zamaloa, Maria C.; Cúneo, Néstor Rubén; Wilf, Peter; Johnson, Kirk R.
Proteaceae are restricted to the Southern Hemisphere, and of the seven tribes of the subfamily Grevilleoideae, only three (Macadamieae, Oriteae, and Embothrieae) have liv- ing members in Argentina. Megafossil genera of Proteaceae recorded from Patagonia in- clude Lomatia, Embothrium, Orites, and Roupala. In this report, we evaluate and revise fossil Argentine Proteaceae on the basis of type material and new specimens. The new col- lections come from the Tufolitas Laguna del Hunco (Early Eocene, Chubut Province), the Ventana (Middle Eocene, Río Negro Province), and the Río Ñirihuau (late Oligocene- early Miocene, Province Río Negro) formations, Patagonia, Argentina. We conﬁrm the presence of Lomatia preferrugineaBerry, L. occidentalis(Berry) Frenguelli, L. patago- nicaFrenguelli, Roupala patagonicaDurango de Cabrera et Romero, and Orites bivascu- larisRomero, Dibbern et Gandolfo. Fossils assigned to Embothrium precoccineumBerry and E. pregrandiﬂorumBerry are doubtful, and new material is necessary to conﬁrm the presence of this genus in the fossil record of Patagonia. A putative new fossil species of Proteaceae is presented as Proteaceae gen. et sp. indet. Fossil Proteaceae are compared with modern genera, and an identiﬁcation key for the fossil leaf species is presented. Doubtful historical records of Proteaceae fossils for the Antarctic Peninsula region and Patagonia are also discussed. Based on this revision, the three tribes of Proteaceae found today in Argentina were already present in Patagonia by the early Eocene, where they probably arrived via the Australia-Antarctica-South America connection. La family Proteaceae está restringida al Hemisferio Sur, y en Argentina solo tres (Macadamieae, Oriteae y Embothrieae) de las siete tribus de la subfamilia Grevilleoideae están representadas. En Patagonia, megafósiles asignados a Proteaceae incluyen los géneros Lomatia, Embothrium, Orites y Roupala. En este trabajo, se evalúan y revisan todos los registros fósiles de Proteaceae para Argentina basado en el ...